APLIKASI OVERALL EQUIPMENT EFFECTIVENESS (OEE) DALAM UPAYA MENGATASI TINGGINYA DOWNTIME PADA STASIUN KETEL DI PG X JAWA TIMUR - Mahros Darsin (MULTITEK INDONESIA, 2020)
PG X in Jember is one of the agro-industries that processing sugar cane into sugar crystals. This factory works seasonally. To ensure the consumer demand for sugar, the sugar factory should operate efficiently during their production season. In fact, it was found that at the downtime at the boiler department at this factory was up to 181 hours for six months production period in the year 2018. This happened mainly in the bagasse conveyor section. This paper is focused on efforts to find out the cause of the high downtime and its possible solution. Overall Equipment Effectiveness (OEE) analysis was employed for measuring machine effectiveness. It is found that the lowest OEE value of 68.27% was in June, while the highest one up to 98.46% was reached in September. The most affecting factor to the low OEE value is reducing speed losses. It affected by 46% to the overall six big losses factors. Based on fishbone analysis, the main cause of the high value of reducing speed losses is lack of supervision in transporting bagasse to the conveyor. The inappropriate dimension of the scrapper (a part of the conveyor) is another reason. Therefore, it is recommended to increase supervision in transporting bagasse to the conveyor. Another recommendation is to reduce the scrapper length. Analysis of the free body diagram of this element shows that reducing its length from 1.215 mm to 1.195 mm will reduce the displacement from 6.67 mm to 4.72 mm without degrading the function of this part.